Survey of block chain - Xin SHEN; Qing-qi PEI; Xue-feng LIU (网络与信息安全学报)
With the wide spread of Bitcoin,block chain serving as the building block of digital currency becomes a hot spot in industry and academia.Due to the decentration of network,the unforgeability of block data,etc.,block chain has attracted more and more attentions from financial institutions.The essential theory and core technique of block chain were surveyed,and the issues of management and security problems of block chain based applications were discussed.To help improve the block chain techniques is the goal.